2008
DOI: 10.3892/or.19.1.229
|View full text |Cite
|
Sign up to set email alerts
|

A peptide derived from alpha-fetoprotein inhibits the proliferation induced by estradiol in mammary tumor cells in culture

Abstract: This study was aimed to obtain additional information on the activity of a cyclized 9-amino acid peptide (cP) containing the active site of alpha fetoprotein, which inhibits the estrogen-stimulated proliferation of tumor cells in culture and of xenografts in immunodeficient mice. Breast cancer cells cultured in the presence of 2 nM estradiol were exposed to cP for different periods and their proliferation, estradiol binding parameters, clustering tendency and expression of E-cadherin and p21Cip1 were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 30 publications
3
15
0
Order By: Relevance
“…We avoided the use of steroid stimulation so as to preclude any trophic effects of steroids on the MCF-7 cells. In other work (36)(37)(38)(39), as well as in this report, we have shown that E 2 stimulates the growth of MCF-7 and T47D cells; it certainly does not inhibit proliferation. As shown clearly in Fig.…”
Section: Discussionsupporting
confidence: 78%
“…We avoided the use of steroid stimulation so as to preclude any trophic effects of steroids on the MCF-7 cells. In other work (36)(37)(38)(39), as well as in this report, we have shown that E 2 stimulates the growth of MCF-7 and T47D cells; it certainly does not inhibit proliferation. As shown clearly in Fig.…”
Section: Discussionsupporting
confidence: 78%
“…The peptide was effective slowing-down the proliferation of estrogen-dependent tumor cells, though not that of estrogen-independent MDA-MB231 cells. The cP did not increase the MCF7 cell death rate, nor altered cell E 2 binding capacity, nor modified cell aromatase activity (20).…”
Section: Introductionmentioning
confidence: 73%
“…Whereas in the proliferation studies under serum-free conditions, the cells were transferred to DMEM F12 containing ITS (insulin, transferrin, selenium), 3% hydroxyethylated starch (HAES), 0.5% human serum albumin, 50 U/ml penicillin and 50 μg/ml streptomycin. The E 2 -insensitive cell line MDA-MB231 (HTB-26; ATCC, USA), used for control studies, was cultured as described previously (20). In each of the experiments, the cells were incubated at 37˚C in a humidified incubator, under a 5% CO 2 atmosphere.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…AFPep does neither of these but does interfere with the phosphorylation of the ER, particularly at Ser 118 (64) but not at Ser 167 or Ser 104 (62). Unlike tamoxifen, AFPep does not alter the number of binding sites or their affinity for radiolabled estrogen (65,67,68 (67). AFPep interfered markedly with the regulation of mitogen-activated protein kinase (MAPK) by activated c-erbB2; it showed no effect on estrogen-stimulated release of matrix metalloproteinases 2 and 9 (69).…”
Section: Afpep Has a Unique Mechanism Of Actionmentioning
confidence: 93%